The development of a contextualised evidence-based clinical practice guideline for the primary health care of chronic musculoskeletal pain in the Western Cape - Ernstzen, Dawn Verna (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.